IMPROVING A MATHEMATICAL MODEL FOR ASSESSING THE EFFECT OF ROUTE LENGTH ON URBAN BUS SERVICE REGULARITY (Ustozlar uchun, 2026)
The regularity of urban bus movement is one of the main indicators of public transport quality, since it directly affects passenger waiting time, transfer reliability, and the operational stability of the route network. In practice, however, regularity is influenced by many factors, among which route length occupies a special place. As the length of a route increases, the number of stops, intersections, traffic conflicts, and accumulated delays also increases, which leads to a deterioration in service regularity. This paper develops an improved mathematical approach for assessing the influence of route length on the regularity of urban bus service. The proposed approach combines the basic regularity coefficient with a route-length sensitivity coefficient obtained from correlation and regression analysis. For model verification, a pilot dataset of urban routes with different operational lengths was analyzed. The obtained regression equation showed a stable inverse relationship between route length and regularity: , where  is the regularity level in percent and  is the route length in kilometers. The coefficient of determination was , which confirms the practical suitability of the model. The results show that each additional kilometer of route length leads, on average, to a decrease in regularity by 1,34 percentage points. The developed model can be used in planning, route design, and dispatch control of urban bus transport.